ANALISIS PEMBEBANAN JEMBATAN BH-1979 JALUR KERETA API BANDARA YIA - ZAKI AFLAH RAMADHAN; LILIS ZULAICHA; ISMANTO HS (ReTII, 2021)
Yogyakarta International Airport, is a new airport which built because Adisucipto Airport exceeds operating capacity. But, the existence of a new airport in Kulon Progo raises several new problems, one of which is the accessibility of public transportation. The ease of accessibility of public transportation, especially trains is very important, so that in 2020 the YIA Airport Railway construction project began. One of the bridges used on the YIA Airport Railway is the WTP Double which is steel bridge. It will review the design of the plate girder from the BH-1979 Bridge which is a WTP Double bridge located at stationing 0+175. The method used in the completion of this final project begins with observing the BH-1979 Bridge, then taking data from Istaka-Catur-Mina, KSO. Furthermore, the calculation of the load using PM Nomor 60 Tahun 2012 and SNI 2833:2016 and analyzed using SAP2000. The results of the analysis obtained are, Vu = 214,834 kN and Mu = 470,472 kNm on Stringer Beam. Then, Vu = -596,926 kN and Mu = 1.490,0013 kNm on Floor Beam. Latest Vu = 1.559,721 kN and Mu = 9.798,9593 kNm on Main Girder. Keywords: Plate Girder, Railway Bridge, Steel Bridge, Yogyakarta International Airport